The Establishment of Double-Transgenic Mice that Co-Express the appA and MxA Genes Mediated by Type A Spermatogonia In vivo - Li-jing BAI; Hui-ming JU; Yu-lian MU; Shu-lin YANG; Hong-yan REN; Hong AO; Chu-duan WANG; Kui LI (Journal of Integrative Agriculture)
Type A spermatogonial stem cells are the only immortal diploid cells in the postnatal animal that undergo self-renewal through the lifetime of an animal and transmit genes to subsequent generations. In this paper, the generation and characterization of double-transgenic mice co-expressing the Escherichia coli appA gene and human MxA gene generated via the in vivo transfection of type A spermatogonial cells were reported for the first time. The dicistronic expression vector pcDNA-appA-MxA(AMP) and ExGen500 transfection reagent were injected into the testicular tissue of 7-d-old male ICR mice. The mice that underwent testis-mediated gene transfer were mated with wild-type female mice, and the integration and expression of the foreign genes in the offspring were evaluated. Transgenic mice that co-expressed appA and MxA showed a gene integration rate of 8.89% (16/180). The transgenic mice were environmentally friendly, as the amount of phosphorous remaining in the manure was reduced by as much as 11.1% by the appA gene (P<0.05); these animals also exhibited a strong anti-viral phenotype.